Profilling Gaya Belajar Peserta Pelatihan Dasar CPNS melalui Tes VAK - Andra Eka Putra (Journal of Teaching dan Learning Research, 2020)
Abstract: [English]This research aims to determine the learning styles of 2019 CPNS basic training participant in Tanah Laut district totalling 156 people. The Instrument that been used un this research was a google form learning basic questionnaire which refers to De Porter & Hernacki’s learning styles theory, which are visual, auditory and kinesthetic learning styles. Based on this research, it is known that 40 participants tend towards visual learning style, 55 participants have a tendency to auditory learning style, 48 participants have a tendency to kinesthetic learning style, and 13 participants have a tendency to mixed learning style. Therefore, it can be said that the majority of CPNS basic training participants in Tanah Laut district have a propensity to auditory learning styles. With this participant learning style profiling, it will be easier for lectures to choose the learning methods that will be used in face-to-face studying so that the training materials can be optimal.Abstrak[indonesia]Penelitian ini bertujuan untuk mengetahui gaya belajar peserta pelatihan dasar CPNS Kabupaten Tanah Laut tahun 2019 berjumlah sebanyak 156 orang. Instrumen yang digunakan dalam penelitian ini adalah angket gaya belajar De Porter & Hernacki yaitu gaya belajar visual, auditori, dan kinestetik. Berdasarkan hasil penelitian, diketahui bahwa 40 orang peserta mempunyai kecendrungan gaya belajar visual, 55 orang peserta mempunyai kecendrungan gaya belajar auditori, 48 orang peserta mempunyai kecendrungan gaya belajar kinestetik, dan 13 orang peserta mempunyai kecendrungan gaya belajar campuran. Oleh sebab itu, daat dikatakan secara mayoritas, peserta pelatihan dasar CPNS Kabupaten Tanah Laut memiliki kecendrungan gaya belajar auditori. Dengan adanya profiling gaya belajar peserta ini, akan memudahkan widyaiswara untuk memilih metode belajar dalam tatap muka pelatihan agar materi mata pelatihan dapat terserap secara optimal.